Responses of soil carbon sequestration to climate‐smart agriculture practices: A meta‐analysis. (16th May 2019) - Bai, Xiongxiong; Huang, Yawen; Ren, Wei; Coyne, Mark; Jacinthe, Pierre‐Andre; Tao, Bo; Hui, Dafeng; Yang, Jian; Matocha, Chris
Abstract: Climate‐smart agriculture (CSA) management practices (e.g., conservation tillage, cover crops, and biochar applications) have been widely adopted to enhance soil organic carbon (SOC) sequestration and to reduce greenhouse gas emissions while ensuring crop productivity. However, current measurements regarding the influences of CSA management practices on SOC sequestration diverge widely, making it difficult to derive conclusions about individual and combined CSA management effects and bringing large uncertainties in quantifying the potential of the agricultural sector to mitigate climate change. We conducted a meta‐analysis of 3, 049 paired measurements from 417 peer‐reviewed articles to examine the effects of three common CSA management practices on SOC sequestration as well as the environmental controlling factors. We found that, on average, biochar applications represented the most effective approach for increasing SOC content (39%), followed by cover crops (6%) and conservation tillage (5%). Further analysis suggested that the effects of CSA management practices were more pronounced in areas with relatively warmer climates or lower nitrogen fertilizer inputs. Our meta‐analysis demonstrated that, through adopting CSA practices, cropland could be an improved carbon sink. We also highlight the importance of considering local environmental factors (e.g., climate and soil conditions and their combination with other management practices) in identifying appropriate CSA practices for mitigating greenhouse gas emissions while ensuring crop productivity. Abstract : We conducted a global meta‐analysis to examine changes in soil organic carbon sequestration induced by three common climate‐smart agriculture (CSA) management practices (i.e., conservation tillage, cover crops, and biochar) and associated environmental controlling factors. Our results demonstrate that croplands could serve as an improved carbon sink and provide climate benefits by adopting these CSA practices. However, climate and soil conditions, as well as the combined effects of multiple management practices, should be proactively considered in scaling up these CSA practices to local and regional levels for achieving climate mitigation and adaptation while ensuring crop security and soil health.